Efficacy and Tolerability of Erlotinib 100 mg/d vs. Gefitinib 250 mg/d in EGFR-Mutated Advanced Non-small Cell Lung Cancer (E100VG250): An Open-Label, Randomized, Phase 2 Study - Zhao, Shen; Zhang, Zhen; Fang, Wenfeng; Zhang, Yaxiong; Zhang, Zhonghan; Hong, Shaodong; Ma, Yuxiang; Zhou, Ting; Yang, Yunpeng; Huang, Yan; Zhao, Hongyun; Zhang, Li (Frontiers in Oncology, 2020)
Abstract Background: Erlotinib-based combination therapy leads to increased efficacy but also toxicity for EGFR-mutated NSCLC. Reducing dose of erlotinib could improve treatment tolerability, but few evidence are available regarding its efficacy at reduced dose. This randomized phase 2 study intends to investigate noninferiority of lower dose erlotinib (100mg/d) versus standard dose gefitinib (250mg/d) in EGFR-mutated NSCLC. Methods: Patients with EGFR-mutated advanced NSCLC were randomized at 1:1 ratio to receive erlotinib 100mg/d or gefitinib 250mg/d until disease progression or unacceptable toxicity. The primary endpoint was disease control rate (DCR). Trial registration: NCT01955421. Results: Between April 2013 and September 2018, 171 patients were randomized to receive erlotinib (n=85) and gefitinib (n=86). 74 in the erlotinib group and 83 in the gefitinib group were include in analysis. DCR with erlotinib and gefitinib were 91% [95%CI 81.7-95.3] and 93% [85.1-96.6], respectively (P=0.613). Response rate was 62% [50.8-72.4] in the erlotinib group and 53% [42.4-63.4] in the gefitinib group (P=0.247). No significant difference was observed between erlotinib and gefitinib in median progression-free survival (10.1 vs 11.3 months, HR=1.295 [0.893-1.879], P=0.171) and median overall survival (26.6 vs 28.7 months, HR=0.999 [0.637-1.569], P=0.998). Subgroup analyses by line of treatment, EGFR subtypes and status of CNS metastasis found similar results. More toxicity (any-grade, 80[96%] vs. 66[89]; grade 3-4, 11[13%] vs. 4[5%]) and toxicity-related discontinuation (10[12%] vs. 3[4%]) occurred with gefitinib compared with erlotinib. But no significant difference was observed. Conclusion: Lower dose erlotinib (100mg/d) was noninferior to standard dose gefitinib (250mg/d) in terms of efficacy in EGFR-mutated NSCLC.